ANALISIS PENERAPAN PAJAK KARBON DAN ULEZ TERHADAP PENURUNAN EMISI KARBON DI INDONESIA - Putu Dian Pusparini; I Gede Widyana; Salsabila Zera Pharresia; M. Hit Fawlung (JURNAL PAJAK INDONESIA, 2023)
The quick effect of climate change has become the main focus of the world including the government of Indonesia. The Government of Indonesia has projected the transition of fossil fuel vehicles to electric vehicles will be a solution in carbon emission reduction. However, in fact electric vehicles still produce carbon emission. The purpose of this research is to compare two policy of carbon emission reduction which both of them have not implemented yet in Indonesia, namely Carbon Tax and Ultra Low Emission Zone. The research method used is qualitative with scoping review approach using various scientific articles. This study concluded that Carbon Tax is more effective and efficient implemented in Indonesia according to 3 (three) variables namely carbon emission reduction, potential tax revenue and implementation efficiency.